2005
DOI: 10.1200/jco.2005.05.153
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Meaningful Improvement in Symptoms and Quality of Life for Patients With Non-Small-Cell Lung Cancer Receiving Gefitinib in a Randomized Controlled Trial

Abstract: PURPOSE Evaluation of disease-related symptom improvement rate by the Lung Cancer Subscale (LCS) of the Functional Assessment of Cancer Therapy-Lung (FACT-L) questionnaire was a coprimary end point of the pivotal phase II trial of gefitinib (Iressa; AstraZeneca, Wilmington, DE) conducted in the United States. This report includes the results of analyses exploring the relationship between weekly LCS scores and radiographic response and survival, as well as detailed protocol-specified analysis of symptom and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 7 publications
6
65
2
Order By: Relevance
“…In the present study, the OS was 29.2 months, which was much longer than that in three previous retrospective reports [19,30,31] focusing on patients who had responded to gefitinib (16 to 20.3 months). Differences in gender, never-smoked status, presence of adenocarcinoma, and ethnicity may be responsible in part for the altered outcome between the responders in the present study and those in the three previous studies.…”
Section: Discussioncontrasting
confidence: 42%
“…In the present study, the OS was 29.2 months, which was much longer than that in three previous retrospective reports [19,30,31] focusing on patients who had responded to gefitinib (16 to 20.3 months). Differences in gender, never-smoked status, presence of adenocarcinoma, and ethnicity may be responsible in part for the altered outcome between the responders in the present study and those in the three previous studies.…”
Section: Discussioncontrasting
confidence: 42%
“…As to their report, the response rates were 64.7% and 81.3% and the timeto-partial response were 40 and 20 days respectively, with evaluation limited to patients with a response. Other studies have also reported that the median time to symptomatic relief was observed within 2-3 weeks for patients treated with EGFR TKIs (18,19). These results suggest that TKI can be considered as the first choice if the primary goal was to achieve prompt symptomatic relief.…”
Section: Palliative Radiotherapy In Advanced Nsclc Treated With Egfr Tkisupporting
confidence: 48%
“…When patients were treated with gefitinib monotherapy in other trials, QoL and symptom improvement were rapid and were correlated with tumor response and survival [26,27]. In the BR.21 study using unselected patients, another EGFR TKI, erlotinib, also improved tumor-related symptoms and important aspects of QoL such as physical functioning [28].…”
Section: Discussionmentioning
confidence: 99%